A successful nursing education promotes newly graduated nurses' job satisfaction one year after graduation: a cross-sectional multi-country study - Sanna Koskinen; Anna Brugnolli; Pilar Fuster-Linares; Susan Hourican; Natalja Istomina; Helena Leino-Kilpi; Eliisa Löyttyniemi; Jana Nemcová; Gabriele Meyer; Célia Simão De Oliveira; Alvisa Palese; Marília Rua; et al. (BMC, 2023)
Abstract Background Job satisfaction is a key factor for the successful transition of newly graduated nurses (NGNs) and for retaining NGNs in their workplaces. However, there is limited evidence of the relationship between satisfaction regarding the nursing education program and NGNs' job satisfaction in the first year after graduation. Therefore, this study aims to examine the association of the nursing education related factors and NGNs' job satisfaction. Methods A cross-sectional study design with the utilization of data collected from the same respondents one year earlier as educational factors was applied. The data were collected from NGNs (n = 557) in 10 European countries using an electronic survey between February 2019 and September 2020, and analyzed in detail for four countries (n = 417). Job satisfaction was measured with three questions: satisfaction with current job, quality of care in the workplace, and nursing profession. Nursing education related factors were satisfaction with nursing education program, level of study achievements, nursing as the 1st study choice, intention to stay in nursing, and generic nursing competence. The data were analyzed statistically using logistic regression. Results Most of the NGNs in the 10 countries were satisfied with their current job (88.3%), the quality of care (86.4%) and nursing profession (83.8%). Finnish, German, Lithuanian and Spanish NGNs' satisfaction with the nursing education program at graduation was statistically significantly associated with their job satisfaction, i.e., satisfaction with their current job, the quality of care, and the nursing profession. Moreover, NGNs who had fairly often or very often intention to stay in nursing at graduation were more satisfied with their current job, with the quality of care, and with the nursing profession compared with NGNs who had never or fairly seldom intention to stay in nursing at graduation. Conclusions Nursing education plays a significant role in NGNs' job satisfaction one year after graduation, indicating the importance to start career planning already during nursing education. Both nursing education providers and healthcare organizations could plan in close collaboration a transition program for NGNs to ease the transition phase and thus increase the NGNs' job satisfaction and ultimately the high-quality care of the patients.